ByzRev 06.2024.060: Alexander Olson, Environment and Society in Byzantium, 650–1150.: Between the Oak and the Olive. Cham: Palgrave Macmillan 2020. - Simeonov, Grigori (The Byzantine Review, 2024)
Alexander Olson, Environment and Society in Byzantium, 650–1150. Between the Oak and the Olive. Cham: Palgrave Macmillan 2020. 258 S. – ISBN 978-3-030-59935-5